Kelayakan Limbah Karung Goni sebagai Bahan Dasar Pembuatan Hiasan Kepala (Headpiece) - Nesya Dinda Sabilla; Ifa Nurhayati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the suitability of burlap sack waste as a raw material for headpieces. This study used a quantitative descriptive approach with a one-shot case study model to test the product's suitability. The assessment process was conducted in two stages: a product validity test by three expert panelists and a preference test by 20 moderately trained panelists. The validity test aimed to assess the product's technical aspects, including shape, neatness, strength, color, and finish. The validity test results showed an average score of 93%, categorized as